Optimizing structural steel bridge design: a study of wind load analysis using STAAD Pro / Ummu Syahirah Mohamad ... [et al.] - Mohamad, Ummu Syahirah; Md Noh, Nur Ilya Farhana; Ja'afar, Muhd Salmizi; Ng, Jing Lin; Razman, Ruzaimah; Surol, Salihah; Hashim, Wardati; Mohammad Azmi, Mohamad Azim (School of Civil Engineering, 2025)
In today’s construction industry, time is often valued more than money, and advanced construction techniques are continually evolving to reduce project durations. Steel structural buildings are considered a revolutionary development in modern construction due to their quick erection process. This study aims to assist engineers in selecting the most suitable construction methods based on site conditions and structural requirements. The primary objective is to analyze the impact of load combinations and load cases on steel structures under wind pressure. Additionally, the study seeks to optimize section properties by selecting appropriate steel structure sizes. In this project, the design and analysis of three different steel structure sizes and materials were conducted using STAAD Pro V8i SS6 software. The analysis demonstrates that Load Combination 2 effectively evaluates structural performance under wind pressure by assessing member forces and stresses. Furthermore, the results indicate that different load cases significantly influence internal forces and stresses, providing crucial insights into structural integrity and performance assessment. This study highlights the substantial impact of wind load on structural steel bridge performance, particularly in terms of axial and shear force variations. Through STAAD Pro analysis, optimal section sizes are identified to enhance strength and stability, offering an improved approach for bridge design. Future research should explore material variations and experimental validations to further optimize structural resilience.